Optimasi Formulasi Sediaan Handbody Lotion Ekstrak Daun Teh Hijau (Camellia Sinensis Linn) - slamet, slamet; U, Waznah (Pena Medika Jurnal Kesehatan, 2020)
Introduction: The outer part of the human body is the skin. This skin has an important function to prevent dehydration, prevent the transition / free radicals, maintain body temperature and as a medium to control stimulation (Wasiaatmadja, 1997). The skin also needs treatment so that free radicals are not known from natural ingredients. The aim of this experiment is optimizing the preparation of hand body lotion from tea leaf extract. Some compositions were chosen which were previously oriented to get good preparation consistency. Method: The method used by mixing part A which consists of cetil alcohol, lanolin, stearic acid heated to 700c, and part B consists of glycerol, triethanolamine, paraben metal and aquadest which were also heated at the same temperature, then stirred until homogeneous and tea leaf extract was added. Then, the hand body lotion produced was tested. Result :The test results of hand body lotion showed a stable preparation from testing for 3 weeks with a semi-solid form, green colour, aroma of tea, and homogenity, pH of preparation 7, dispersion test : 2.8 x3.1 cm2 - 7x8 cm2, adhesion test : 0.73 seconds - 02.3 seconds. The result of irritation test showed that the hand body lotion is safe or non-irritating in 10 respondents. The conclusion of this experiment is the hand body lotion produced is safe according to the requirements. Keywords: Hand body lotion, green tea leaf extract, maceration, skin.